Systemic vasoconstriction and mortality in patients with heart failure and reduced ejection fraction: A cohort of patients who underwent non-invasive hemodynamic monitoring. - Marcelo Eidi Ochiai; Kelly Regina Vieira Novaes; Lucas Hideki Kato Myakava; Marcelo Villaça Lima; Euler Cristovan Ochiai Brancalhão; Juliano Novaes Cardoso; Solange de Sousa Andrade; Wilson Jacob Filho; Antonio Carlos Pereira Barretto (PLoS ONE)
Advanced heart failure primarily manifests during and after hospitalization for decompensation. Identifying prognostic factors is crucial for distinguishing patients who may benefit from drug therapy from those with end-stage disease. This study aimed to evaluate the prognostic significance of systemic vasoconstriction in patients with decompensated heart failure with a reduced ejection fraction. We evaluated patients hospitalized for decompensated heart failure with a left ventricular ejection fraction of < 40% who underwent non-invasive hemodynamic monitoring using the Modelflow method. The primary endpoint was all-cause mortality, and the data were analyzed using logistic regression. This study included 58 patients (71% men) with a mean age of 58.9 years, an ejection fraction of 23.4%, a median B-type natriuretic peptide of 1,005.0 pg/mL (interquartile range = 1,498.0), and 43% with Chagas disease. The cardiac index was 2.7 L∙min-1∙m-2, and the systemic vascular resistance index was 2,403.9 dyn∙s∙cm-5∙m-2. Over an average follow-up of 29.0 months, 51 (87.9%) patients died. Assessing three-year mortality, high systemic vascular resistance indices were predictive of events with a relative risk of 3.9 (95% confidence interval = 1.1-13.9; P-value = 0.037). In conclusion, non-invasive hemodynamic monitoring identifies systemic vasoconstriction, which is associated with poor prognosis in patients with advanced heart failure and reduced ejection fraction.